Long Non-coding RNA Uc.48+ Small Interfering RNA Alleviates Neuroinflammatory Hyperalgesia in Gp120-Treated Rats via the P2Y12 Receptor - Peng, Lichao; Wu, Bing; Shi, Liran; Zou, Lifang; Li, Lin; Yang, Runan; Xu, Xiumei; Li, Guilin; Liu, Shuangmei; Zhang, Chunping; Liang, Shangdong (Frontiers in Neuroscience, 2021)
Human immunodeficiency virus (HIV) envelope glycoprotein 120 (gp120) leads to hyperalgesia. Long noncoding RNAs (lnc RNAs) are characterized by the lack of a protein coding sequence and may contribute to the development and maintenance of inflammatory and neuroinflammatory pain. Herein, we report that lncRNA uc.48+ siRNA regulates purinergic 2 (P2) Y12 receptor on HIV gp120-induced neuroinflammatory pain in rats. LncRNA uc.48+ increased in the dorsal root ganglia (DRG) of gp120-treated rats, which was accompanied by intensified pain behaviors, and small interfering RNA (siRNA) that targets uc.48+ markedly alleviated hyperalgesia in gp120-treated rats. Notably, uc.48+ overexpression increased P2Y12 expression in control rats DRG and induced hyperalgesia. Uc.48+ siRNA inhibited P2Y12 expression in gp120-treated rats. Uc.48+ potentiated P2Y12 receptor functions in the neurons and heterologous cells. Therefore, uc.48+ siRNA treatment reduced the upregulation of P2Y12 expression and function in DRG neurons, and, hence, alleviated hyperalgesia in gp120-treated rats.